Obstetric anesthesiology : an illustrated case-based approach - Husain, Tauqeer, 1979-; Fernando, Roshan; Segal, Scott, (Cambridge medicine (Series), 2019)
The complex healthcare needs of pregnant patients, where care is tailored to not one but two patients, pose specific challenges to anesthesiologists. This book provides concise, case-based discussion on the clinical scenarios and challenges faced in the provision of anesthesia and pain relief for expectant mothers. In the style of problem-based learning, each case is presented as a short scenario, followed by discussion of the causes, risk factors, management and controversies involved. The textbook features a wide range of cases, from common clinical scenarios that are experienced in day-to-day practice to the rare but significant pathologies less familiar to most clinicians. With a global base of contributors, the book is relevant to practice across the world. The concise format supports both trainee anesthesiologists in their initial experiences of obstetrics and exam preparation, and experienced clinicians in need of a reliable, quick-reference text.